Intra-host Symbiont Diversity and Extended Symbiont Maintenance in Photosymbiotic Acantharea (Clade F) - Mars Brisbin, Margaret; Mesrop, Lisa Y.; Grossmann, Mary M.; Mitarai, Satoshi (Frontiers in Microbiology, 2018)
Photosymbiotic protists contribute to surface primary production in low-nutrient, open-ocean ecosystems and constitute model systems for studying plastid acquisition via endosymbiosis. Little is known, however, about host-symbiont dynamics in these important relationships, and whether these symbioses constitute mutualisms is debated. In this study, we applied singl¬e-cell sequencing methods and advanced fluorescent microscopy to investigate host-symbiont dynamics in clade F acantharians, a major group of photosymbiotic protists in oligotrophic subtropical gyres. We amplified the 18S rRNA gene from single acantharian hosts and environmental samples to assess intra-host symbiont diversity and to determine whether intra-host symbiont community composition directly reflects the available symbiont community in the surrounding environment. Our results demonstrate that clade F acantharians simultaneously host multiple species from the haptophyte genera Phaeocystis and Chrysochromulina. The intra-host symbiont community composition was distinct from the external free-living symbiont community, suggesting that these acantharians maintain symbionts for extended periods of time. After selectively staining digestive organelles, fluorescent confocal microscopy showed that symbionts were not being systematically digested, which is consistent with extended symbiont maintenance within hosts. Extended maintenance within hosts may benefit symbionts through protection from grazing or viral lysis, and therefore could enhance dispersal, provided that symbionts retain reproductive capacity. The evidence for extended symbiont maintenance therefore allows that Phaeocystis could glean some advantage from the symbiosis and leaves the possibility of mutualism.